Psychoanalysis on Conflict of the Main Character Joe Goldberg in TV Series You Season 3 - Ni Luh Putu Widi Saraswati; Ketut Artawa; Ni Made Ayu Widiastuti (Udayana University, 2022)
The purpose of this research is to examine the character of Joe Goldberg in the television series You will learn about the challenges Joe Goldberg confronts and how his character resolves them from a psychoanalytic perspective. This study employs a qualitative approach, as qualitative research focuses on qualitative phenomena. The purpose of this research is to ascertain how individuals feel or think about a certain issue or institution. Additionally, this study employs two theories: the first is from Sigmund Freud and is referred to be the model of the mind; the second is from Kenney and is referred to as the forms of conflict. Following that, this study discovered that conflict between a single man and conflict between men happened mostly in Joe Goldberg's character. Meanwhile, when Joe Goldberg is attempting to solve an issue, his id, ego, and superego all play a significant part.